2013
DOI: 10.3109/00365521.2012.746395
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: symptoms of rebound acid hypersecretion following proton pump inhibitor treatment

Abstract: Gastric acid rebound hypersecretion following PPI therapy induces reflux-like symptoms post-treatment in asymptomatic volunteers, but the significance of this in patient populations is not clear. The studies in patients with reflux disease found no evidence of symptomatic RAHS, but these studies were hampered by severe methodological weaknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 32 publications
1
43
2
8
Order By: Relevance
“…In this study, the proportion of patients who were on long-term PPI (26%) was higher 209 than that reported in previous studies [16][17][18] 34 . The issue of appropriateness in terms of prescription practices has been discussed 229 in existing literature 29,35,36 .…”
contrasting
confidence: 54%
“…In this study, the proportion of patients who were on long-term PPI (26%) was higher 209 than that reported in previous studies [16][17][18] 34 . The issue of appropriateness in terms of prescription practices has been discussed 229 in existing literature 29,35,36 .…”
contrasting
confidence: 54%
“…1 A systematic review published in 2013 showed that in 3 of the 5 included studies (which were conducted in asymptomatic volunteers), rebound hypersecretion of gastric acid occurred after discontinuation of PPI therapy. 32 Therefore, use of tapering as a PPI discontinuation strategy may prevent rebound hypersecretion and may increase patient comfort with deprescribing. Randomized controlled trials comparing various discontinuation strategies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although baclofen can reduce the number of reflux events by inhibiting transient relaxations of the lower oesophageal sphincter, long-term data are lacking 15 and adverse effects such as drowsiness occur in up to 63% of patients. 16 Other drugs are currently under investigation, 15,25 but there do not appear to be any 'game changers' in the pipeline.…”
Section: Medical Managementmentioning
confidence: 99%
“…There may be a period of acid hypersecretion following the withdrawal of PPI, but any symptoms will reduce over a period of about a month, after which recurring symptoms are most likely to be due to underlying reflux disease. 16 Using a PPI when required will be adequate for some patients, however 75-90% will relapse over six months. 5 This reflects the chronic nature of the condition rather than a failure of treatment.…”
Section: Maintenance Therapymentioning
confidence: 99%